MENINGKATKAN LOYALITAS PADA TINJAUAN KEPERCAYAAN DAN KOMITMEN: PERSPEKTIF PADA NASABAH BANK SYARIAH INDONESIA DI KANTOR CABANG BANDA ACEH - Setia Budi, M. Arief (Fakultas Ekonomi, 2024)
This study aims to determine the effect of customer trust and customer commitment on customer loyalty both partially and simultaneously on Bank Syariah Indonesia Customers at the Banda Aceh Branch Office. This study uses a quantitative approach. The analysis method used is multiple linear regression analysis using SPSS 25. The results of the study indicate that partially customer trust has an effect on customer loyalty. Customer commitment also partially has an effect on customer loyalty. Simultaneously customer trust and customer commitment have an effect on customer loyalty